A LEGAL REVIEW OF CONSUMER PROTECTION IN ELECTRONIC TRANSACTIONS - Putu Gede Sedana Yasa; Putu Eka Trisna Dewi; Cokorde Istri Dian Laksmi Dewi (Warmadewa Press, 2025)
The rapid development of technology has led to advances in all areas, including business and transactions. This ease of doing business is accompanied by the availability of supporting technologies and networks. Electronic transactions (e-commerce) have proved to be a major breakthrough, enabling consumers to save time by eliminating the need to visit a seller’s premises or to interact face-to-face with business operators. Obviously, this convenience leads to greater comfort and satisfaction for consumers, as they do not have to spend excessive amounts of time. On the other hand, this progress also has negative consequences, in particular when problems arise with goods received that do not correspond to the pictures displayed. Disputes can also arise from unsatisfactory relationships between consumers and traders. The underlying problem is that consumer protection is not comprehensively and clearly regulated in the current legislation on online transactions and consumer protection. Therefore, there is a need for more specific legislation to provide adequate legal protection and legal certainty for every citizen. The research method used in this study is normative legal research. The aim of this study is to examine the relationship between consumers and economic operators and the legal protection afforded to consumers in electronic transactions.